2020
DOI: 10.1128/jcm.01215-20
|View full text |Cite
|
Sign up to set email alerts
|

Changing from Clinician-Collected to Self-Collected Throat Swabs for Oropharyngeal Gonorrhea and Chlamydia Screening among Men Who Have Sex with Men

Abstract: The coronavirus (COVID-19) pandemic has led many clinics to move from clinician-collected to self-collected oropharyngeal swabs for the detection of sexually transmitted infections (STIs). Before this change, however, self-collection was primarily used for genital and anorectal infections with only limited studies on the performance of self-collected oropharyngeal swabs for oropharyngeal STIs. Melbourne Sexual Health Centre (MSHC) changed from clinician-collected to self-collected oropharyngeal swabs for oroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…The change to self‐collection of oropharyngeal swabs in clinics across Australia is unlikely to impact diagnoses of Chlamydia trachomatis and Neisseria gonorrhoeae given a previous study in MSM showed no difference in positivity after self‐collection in either infection 19 . However, there was an increase in the proportion of indeterminate results for N. gonorrhoeae but not C .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The change to self‐collection of oropharyngeal swabs in clinics across Australia is unlikely to impact diagnoses of Chlamydia trachomatis and Neisseria gonorrhoeae given a previous study in MSM showed no difference in positivity after self‐collection in either infection 19 . However, there was an increase in the proportion of indeterminate results for N. gonorrhoeae but not C .…”
Section: Discussionmentioning
confidence: 89%
“…The change to self‐collection of oropharyngeal swabs in clinics across Australia is unlikely to impact diagnoses of Chlamydia trachomatis and Neisseria gonorrhoeae given a previous study in MSM showed no difference in positivity after self‐collection in either infection. 19 However, there was an increase in the proportion of indeterminate results for N. gonorrhoeae but not C . trachomatis during the self‐collection period compared to clinician‐collected (1.6% [24/1,497] versus 0.9% [23/2,600]; p=0.038), 19 perhaps due to men not collecting sample thoroughly enough which may potentially translate to an increase in extra clinic visits for repeat tests nationwide for oropharyngeal gonorrhoea.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“… 22 , 23 Fifth, we changed clinician-collected oropharyngeal swabs to self-collected oropharyngeal swabs in March 2020 to minimise the exposure to SARS-CoV-2 among healthcare workers during the COVID-19 pandemic; however, there was no significant difference in oropharyngeal gonorrhoea positivity. 29 …”
Section: Discussionmentioning
confidence: 99%
“…These assays diagnose CT, including LGV, detecting all serovars. NAATs are highly sensitive for detecting CT-DNA/RNA in first void urine and self-taken vaginal, rectal, and pharyngeal swabs; self-collection is well and widely accepted in women and in MSM as shown in prospective and retrospective cohort studies [44][45][46][47][48]. A randomized clinical trial (RCT) in women and MSM showed good concordance between clinician-and self-taken pharyngeal and rectal swabs, with similarly high diagnostic accuracy [49].…”
Section: With Resources Available Ct Is Easy To Testmentioning
confidence: 99%